A polysaccharide from Sargassum fusiforme protects against immunosuppression in cyclophosphamide-treated mice - Chen, Xiaoming; Nie, Wenjian; Fan, Sairong; Zhang, Junfeng; Wang, Yanxing; Lu, Jianxin; Jin, Liqin (Carbohydrate polymers, 2012)
► A water-soluble polysaccharide (SFPS) was isolated and purified from Sargassum fusiforme. ► Structural characterization of SFPS was investigated. ► SFPS stimulated proliferation and cytokines secretion of murine splenic lymphocytes. ► SFPS markedly increased the phagocytic rates and cytokines secretion of peritoneal macrophages. ► SFPS had immunostimulatory effects against cyclophosphamide-induced immunosuppression. A water-soluble polysaccharide (SFPS) isolated from Sargassum fusiforme was purified by DEAE-52 cellulose anion-exchange and Sephadex G-200 gel filtration chromatography. The high performance gel permeation chromatography (HPGPC) analysis showed that the average molecular weight (Mw) of SFPS was 299kDa. The SFPS was composed of d-fucose, l-xylose, d-mannose and d-galactose in a molar ratio of 5.9:1.0:2.3:2.2. The results showed that SFPS stimulated proliferation and the cytokines (IL-2, IL-6 and IFN-γ) secretion of splenic lymphocytes in cyclophosphamide-induced immunosuppressed mice. SFPS markedly increased the phagocytic rates and cytokines (IL-2, IL-6 and TNF-α) secretion of peritoneal macrophages. Administration of SFPS significantly raised spleen index. It could act as an efficacious adjacent immunopotentiating therapy or an alternative means in lessening chemotherapy-induced immunosuppression, and also can be utilized as immunostimulants for food and pharmaceutical industries.